Understanding Trade-Related Aspects of Intellectual Property Rights Agreement: From Hard and Soft Law Perspective - Roisah, Kholis (Hasanuddin University, 2017)
Trade-Related Aspects of Intellectual Property Rights (TRIPs) Agree-ment interesting to be understood in the perspective of hard law and soft law. TRIPs Agreement justified as hard or soft law by identifying the norms in the TRIPs agreement. Parameter obligation of TRIPs agreement visible implementation and enforcement of agreement norm with full compliance to fourth of the IPR Convention for the State parties is an indicator of unconditional obligation. Parameters precision TRIPS agreement showed formulation of general obligation setting up the implementation of treaty obligations is regulated in detail and the use of âshallâ term in any norm, describe the imperative norm character and shown indicator as substantial limited of interpretation with the parties might not interpreted. Parameter delegation looked explicitly provision of implementation and enforcement agreement that put an obligation on national authorities of state parties through domestic law and its courts. Parameter obligation, precision as well as delegation showed as high indicator that the TRIPs agreement characterized as hard law.